Abu al-Hasan Al-Amiri's Comparison of Doctrinal Pillars in Six Religions: In the light of "Al-I’lam bi-Manaqib al-Islam" - kanani, Dr. Iman; Naeem Shafiei (Al Basirah, 2025)
Abu al-Hasan al-Amiri is one of the earliest and most prominent Muslim philosophers from Iran. He is known for his numerous contributions to the field Ilm u Kalam and comparative religion. Among his most significant works, one is Al-Iʿlām bi-Manāqib al-Islām. Along with some other topics about Manaqib al Islam he compares Islam with five other religions: Judaism, Sabianism, Christianity, Zoroastrianism, and idol-worshiping. Various scholars have explored different dimentions of Al Amiri,s contributions, like Fatima Al- Tays, Abdullah Tawaijri and Hanan Mansouri. However all the available literature elaborates biography and general themes of Al Amiri's work. Assessing his way of comparing Islam with other religions remains still unstudied. The doctrinal pillars of these faiths constitute a central theme in his work. However, the lack of sufficient critical studies on al-Amiri’s approach in this regard has motivated the writing of this article. This research focuses on the comparative analysis of doctrinal pillars in Al-Iʿlām, offering detailed explanations and references. In addition to evaluating al-Amiri’s methodology, the study seeks to conduct a thorough and insightful examination of the doctrinal foundations of the aforementioned religions. Al Amiri's has selected four domains for this research, 1: Belief, 2: worship, 3: Public dealings, 4: Punishments. Although He has discussed all of the above domains but the core focus of Abu Al Hasan Al Amiri is on the first two pillars. In his he has criticized the sectarian misrepresentation. He appreciates research and reasoning and discourages blind following. This study suggests to adopt the doctrinal model of comparisons adopted by Abu Al Hasan Amari and by doing so, it will integrate moral and ethical foundation to present day's interfaith dialogues and debates.